(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This paper discusses the legal, ethical, and social aspects of dismissal for due cause of workers in situations of chemical dependency. Recognized as a disease by the OMS, chemical dependency requires an approach that goes beyond punishment, taking into account social, cultural, and public health factors. The application of Article 482 of the CLT is analyzed, especially regarding habitual intoxication or intoxication at work, in light of the Federal Constitution, highlighting that the Superior Labor Court (TST) and the 2nd Regional Labor Court (TRT-2) have acknowledged that dismissals motivated solely by addiction, without prior offer of treatment or support, may be considered discriminatory and null. It is concluded that dismissal for cause in such cases should not be the first measure taken, and principles such as human dignity, the right to health, and social reintegration should prevail, reinforcing the responsibility of companies to adopt a humanized and inclusive approach.